1970
DOI: 10.1115/1.3408660
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Steady-State Vibrations in a High-Speed Slider-Crank Mechanism

Abstract: The research presented in this paper is an analytical study of the vibrations associated with planar mechanical linkages. Specifically, the vibrations of a high-speed slider-crank mechanism with a uniform elastic connecting rod and a rigid crank are studied. The elastic connecting rod, with distributed mass, is taken to be externally, viscously damped with a concentrated mass present at its sliding end. The equations governing the longitudinal and transverse vibrations of the elastic connecting rod are derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1972
1972
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…From a first order perturbational approximation, previous researchers [15,17] have indicated that the response amplitude grows like f22 for low speeds (f~ << 1) and small cranks. This is experimentally verified in Figure 10, where a comparison can be made among peak to peak stress amplitudes from the experimental response, the analytical response of equation (1), and the perturbational approximation represented by the following expression: 4 peak to peak stress = -rf2230…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From a first order perturbational approximation, previous researchers [15,17] have indicated that the response amplitude grows like f22 for low speeds (f~ << 1) and small cranks. This is experimentally verified in Figure 10, where a comparison can be made among peak to peak stress amplitudes from the experimental response, the analytical response of equation (1), and the perturbational approximation represented by the following expression: 4 peak to peak stress = -rf2230…”
Section: Resultsmentioning
confidence: 99%
“…Tadjbakhsh and Yountis [12], and Beale and Lee [13], considered parametric resonance without the restriction of a small crank and removed nonlinearities from the analysis. Other authors have analytically investigated critical speed phenomena (Cleghorn et al [14]) and steady state instability (Jasinski et al [15]) by also dropping nonlinear terms and focusing on linear ordinary differential equations. Lee and Beale [16] presented response case studies that included period doubling and jump bifurcations for small, intermediate, and large crank lengths, with and without the piston mass, and with and without a gas force acting on the piston.…”
Section: Introductionmentioning
confidence: 99%
“…Similar perturbation methods, such as the regular expansion method [12,15] and the method of averaging [10,11], have been applied to study mechanism system. However, all previous investigations have provided only linear results.…”
Section: Discussionmentioning
confidence: 99%
“…By using the method of averaging and assuming a small length ratio, Jasinski et al [10,11] investigated the dynamic stability of a flexible connecting rod in a slider-crank mechanism. Viscomi and Ayre [4] examined the nonlinear bending response of the connecting rod.…”
Section: Introductionmentioning
confidence: 99%
“…During last years, several researches discussed the problems of dynamic and stability of high speed flexible linkage system. The stability and dynamic response of high speed slider crank mechanism with uniform elastic connecting rod and a rigid crank were studied by Jasinski, et al [1]. The Euler-Bernoulli and Timoshenko beams was considered to study the stability of a slider-crank mechanism by Badlani and Kleinhenz [2].…”
Section: Introductionmentioning
confidence: 99%